Manipulation tactics and basic psychological needs - Butković, Ana (2013)
Manipulation tactics represent different ways people try to influence others to do something for them. All people use them and they enable people to get what they need and want. Previous studies have shown that phenotypic correlations between manipulation tactics and personality are due to overlapping genetic factors. This study examined the relationship between manipulation tactics used within twin pairs and satisfaction of basic psychological needs. Data was collected via mail from 338 twin pairs (36 MZM, 49 DZM, 69 MZF, 70 DZF, 114 DZO), aged between 15 and 22 years (M=18.6, SD=2.31). All participants filled in Ryan and Deci’s Basic Psychological Needs Scale and manipulation tactics questionnaire from which scores for three types of manipulation tactics were obtained (indirect tactics for coercion or ITC, direct tactics or DT and indirect tactics for humoring or ITH), as well as a total sum score (TM). Significant phenotypic correlations, in the .11-.24 range, were obtained for TM and need for relatedness, ITC and ITH with need for autonomy and competence, and for DT with all three needs. Cholesky decomposition was used to analyze the relationship between three needs and each type of manipulation tactics, as well as with total score. For ITC, DT and TM analyses showed that phenotypic correlations were due to overlapping non-shared environmental factors, while only for ITH to overlapping genetic factors.